Photocatalytic splitting of CS2 to a carbon-sulfur polymer and S8 catalyzed by a bimetallic ruthenium(II) compound with a tertiary amine binding site - towards photocatalytic splitting of CO2? - Livanov, Konstantin; Madhu, Vedichi; Balaraman, Ekambaram; Shimon, Linda J. W.; Diskin-Posner, Yael; Neumann, Ronny (Inorganic Chemistry, 2011)
The catalytic photocleavage of CS2 to S8 and a (CxSy)n polymer with visible light using a dinuclear ruthenium(II) compound with a bipyridine units for photoactivity and a vicinal tertiary amine binding site for CS2 activation was studied. The catalyst was characterized by X-ray diffraction, 1H NMR, and 13C NMR, ESI-MS and elemental analysis. CS2 photocleavage was significant (240 turnovers, 20 h) to yield isolable S8 and a (CxSy)n polymer. A mononuclear catalyst or one without an amine binding site showed significantly less activity. XPS of the (CxSy)n polymer showed a carbon/sulfur ratio ∼1.5–1.6 indicating that in part both C–S bonds of CS2 had been cleaved. Catalyst was also included within the polymer. The absence of peaks in the 1H NMR verified the (CxSy)n nature of the polymer, while 13C NMR and IR indicated that the polymer had multiple types of C–S and C–C bonds.

PNN-Ru pincer complexes based on phosphinated 2,2’-dipyridinemethane- and 2,2’-oxobispyridine. metal-ligand cooperation in cyclometallation and catalysis - Barrios-Francisco, Rigoberto; Balaraman, Ekambaram; Diskin-Posner, Yael; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2013)
The synthesis of novel PNN ruthenium pincer complexes based on 2,2′-dipyridinemethane phosphine derivatives, as well as on 2,2′-oxobispyridine phosphine ligands, and their reactivity toward dearomatization and cyclometalation are described. The dearomatized compounds 7a,b undergo cyclometalation to yield complexes 8a,b. In order for cyclometalation to proceed, the coordination sphere around the Ru center has to rearrange, and this depends on the flexibility of the system, showing that the cyclometalation is qualitatively faster in the case of the dimethyl derivative 7a than in the case of the spyrocyclopentyl derivative 7b. The cyclometalation occurs diastereoselectively and leads to only one diastereomer of the cyclometalated compounds. In the case of the 2,2′-oxobispyridine complex 6c, the dearomatized complex was too unstable to be isolated; however it was possible to isolate and characterize a stable dicarbonyl-dearomatized ruthenium(II) complex, 9c, when the deprotonation was performed under a CO atmosphere. Dearomatization of 6a under CO also led to dicarbonyl-dearomatized ruthenium(II) complex 9a, which slowly rearranged into the dicarbonyl-aromatized ruthenium(0) complex 10a. These complexes were tested in catalytic alcohol–amine coupling, esterification of primary alcohols, and hydrogenation of secondary amides. Moderate activity was observed in hydrogenation of amides to alcohols and amines and low activity in the other transformations, owing mainly to the formation of stable cyclometalated compounds.

Stepwise metal-ligand cooperation via a reversible aromatization-deconjugation-sequence in ruthenium complexes with a tetradentate phenanthroline-based ligand - Langer, Robert; Fuchs, Ido; Vogt, Matthias; Balaraman, Ekambaram; Diskin-Posner, Yael; Shimon, Linda J. W.; Ben-David, Yehoshoa; Milstein, David (Chemistry - A European Journal, 2013)
The synthesis and reactivity of ruthenium complexes containing the tetradentate phenanthroline-based phosphine ligand 2,9-bis((di-tert-butylphosphino)methyl)-1,10-phenanthroline (PPhenP) is described. The hydrido chloro complex [RuHCl(PPhenP)] (2) undergoes facile dearomatization upon deprotonation of the benzylic position, to give [RuH(PPhenP-H)] (4). Addition of dihydrogen to 4 causes rearomatization of the phenanthroline moiety to trans-[Ru(H)2(PPhenP)] (5), followed by hydrogenation of an aromatic heterocycle in the ligand backbone, to give a new dearomatized and deconjugated complex [RuH(PPhenP*-H)] (6). These aromatization/deconjugation steps of the coordinated ligand were demonstrated to be reversible and operative in the dehydrogenation of primary alcohols without the need for a hydrogen acceptor. This aromatization/deconjugation sequence constitutes an unprecedented mode of a stepwise cooperation between the metal center and the coordinated ligand.

Synthesis, structures, and dearomatization by deprotonation of iron complexes featuring bipyridine-based PNN pincer ligands - Zell, Thomas; Langer, Robert; Iron, Mark A.; Konstantinovski, Leonid; Shimon, Linda J. W.; Diskin-Posner, Yael; Leitus, Gregory; Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Inorganic Chemistry, 2013)
The synthesis and characterization of new iron pincer complexes bearing bipyridine-based PNN ligands is reported. Three phosphine-substituted pincer ligands, namely, the known tBu-PNN (6-((di-tert-butylphosphino)methyl)-2,2′-bipyridine) and the two new iPr-PNN (6-((di-iso-propylphosphino)methyl)-2,2′-bipyridine) and Ph-PNN (6-((diphenylphosphino)methyl)-2,2′-bipyridine) ligands were synthesized and studied in ligation reactions with iron(II) chloride and bromide. These reactions lead to the formation of two types of complexes: mono-chelated neutral complexes of the type [(R-PNN)Fe(X)2] and bis-chelated dicationic complexes of the type [(R-PNN)2Fe]2+. The complexes [(R-PNN)Fe(X)2] (1: R = tBu, X = Cl, 2: R = tBu, X = Br, 3: R = iPr, X = Cl, and 4: R = iPr, X = Br) are readily prepared from reactions of FeX2 with the free R-PNN ligand in a 1:1 ratio. Magnetic susceptibility measurements show that these complexes have a high-spin ground state (S = 2) at room temperature. Employing a 2-fold or higher excess of iPr-PNN, diamagnetic hexacoordinated dicationic complexes of the type [(iPr-PNN)2Fe](X)2 (5: X = Cl, and 6: X = Br) are formed. The reactions of Ph-PNN with FeX2 in a 1:1 ratio lead to similar complexes of the type [(Ph-PNN)2Fe](FeX4) (7: X = Cl, and 8: X = Br). Single crystal X-ray studies of 1, 2, 4, 6, and 8 do not indicate electron transfer from the FeII centers to the neutral bipyridine unit based on the determined bond lengths. Density functional theory (DFT) calculations were performed to compare the relative energies of the mono- and bis-chelated complexes. The doubly deprotonated complexes [(R-PNN*)2Fe] (9: R = iPr, and 10: R = Ph) were synthesized by reactions of the dicationic complexes 6 and 8 with KOtBu. The dearomatized nature of the central pyridine of the pincer ligand was established by X-ray diffraction analysis of single crystals of 10. Reactivity studies show that 9 and 10 have a slightly different behavior in protonation reactions.

Direct synthesis of secondary amines from alcohols and ammonia catalyzed by a ruthenium pincer complex - Balaraman, Ekambaram; Srimani, Dipankar; Diskin-Posner, Yael; Milstein, David (Catalysis Letters, 2015)
Efficient and selective direct synthesis of secondary amines from primary alcohols and ammonia with liberation of water has been achieved, with high turnover numbers and with no generation of waste. In case of benzylic alcohols, imines rather than amines are obtained. This atom economical, environmentally benign reaction is homogenously catalyzed by a well-defined bipyridine based Ru(II)-PNN pincer complex.
Keywords: Alcohol; Ammonia; Homogenous catalysis; Ru-pincer complex; Secondary amine